The Term ‘Zīnah’ (Adornment) in the Noble Qur’an - Adil Elouade (مجلة كلية الشريعة والدراسات الإسلامية, 2025)
Objectives: This study focuses on the Quranic term ‘zīnah’ adornment to examine its conceptual framework, elucidate its meanings, and clarify its significance in relation to human existence. By undertaking this term within its Quranic context, the study seeks to broaden and enhance our understanding and usage of it.